2020
DOI: 10.17582/journal.sja/2020/36.2.459.469
|View full text |Cite
|
Sign up to set email alerts
|

Growth, Yield and Sucrose Percent Response of Sugarcane to Zinc and Boron Application

Abstract: S ugarcane (Saccharum officinarium L.) is a cash produce of our country (GoP, 2018). Sugarcane is also cultivated worldwide in more than 105 countries (Hussain et al., 2015). According to area under cultivation, Pakistan is the 5 th position in cane acreage and production and almost 8 th biggest consumer of sugar in the world (FAO, 2017). Cane is the main and overwhelming raw material used. It could be a key Abstract | Zinc (Zn) and boron (B) are restrictive micronutrients in production regions of the sugarcan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 7 publications
4
9
0
Order By: Relevance
“…). These results can be attributed to the foliar application of micronutrient and NPK, where applied zinc micronutrient is directly involved in the synthesis of tryptophan, a precursor of Indole acetic acid, and the formation of enzymes that are responsible for cell growth and elongation [12]. Normal growth of the plant can be affected due to non-availability of nutrients but foliar application avoids the nutrient fixation and makes it available to the plant on time.…”
Section: Resultsmentioning
confidence: 99%
“…). These results can be attributed to the foliar application of micronutrient and NPK, where applied zinc micronutrient is directly involved in the synthesis of tryptophan, a precursor of Indole acetic acid, and the formation of enzymes that are responsible for cell growth and elongation [12]. Normal growth of the plant can be affected due to non-availability of nutrients but foliar application avoids the nutrient fixation and makes it available to the plant on time.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, soil application of Zn enhanced cane yield (111.9 t ha -1 ) and the foliar application of B resulted produced highest cane yield attributes specifically cane yield (107.4 t ha-1), brix (21.9%). And its interaction effects increased distinctively cane yield (119.0 t ha-1) and brix (24.0%), [21] (Mangrio1 et al, 2020).…”
Section: Effect Of Blended Fertilizers and Levels Of Phosphorus On Sugarcane Juice Qualitymentioning
confidence: 99%
“…Total nitrogen was analyzed by the Micro-Kjeldahl method [15]. The pH of the soil was determined in 1:2.5 (weight/ volume) soil to water dilution ratio using a glass electrode attached to digital pH meter [21]. Cation exchange capacity was measured after saturating the soil with 1N ammonium acetate (NH4OAC) and displacing it with 1N NaOAC [5] Available phosphorus was determined using the Olsen method [23].…”
Section: Soil Analysismentioning
confidence: 99%
“…Marangoni et al (2019), working in soil with low clay and organic matter content in Southeast Brazil, described that the application of B in the form of soluble salt (boric acid) in the planting furrow decreases sugarcane productivity in the first and second crop cycle. However, Mangrio et al (2020) reported that foliar application of boron resulted in a higher ton of stem (119.0 t ha -1 ) and soluble solids content (ºBrix) of 23.0%.…”
Section: Effect Of Micronutrients On Sugarcane Boron (B)mentioning
confidence: 99%